2019
DOI: 10.3390/ijerph16071283
|View full text |Cite
|
Sign up to set email alerts
|

Risks of Ear Complaints of Passengers and Drivers While Trains Are Passing Through Tunnels at High Speed: A Numerical Simulation and Experimental Study

Abstract: Ear complaints induced by interior pressure transients are common experiences for passengers and crew members when high-speed trains are passing through tunnels. However, approaches to assessing the risks of the pressure-related aural discomfort have not been reported until recently. The objective of this study was to evaluate the hazards of interior pressure transients of high-speed train on human ears combining the effects of operation speed and seal index. Moving model tests were conducted to obtain the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Regarding the relationship between noise, train stations and tunnels in terms of public health, Xie, Peng, Wang, and Zhang conducted experiments in tunnels to examine the effects of high-speed rails on hearing [60]. The authors found that acoustic discomfort occurred when a train passed in the middle of the tunnel [60].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the relationship between noise, train stations and tunnels in terms of public health, Xie, Peng, Wang, and Zhang conducted experiments in tunnels to examine the effects of high-speed rails on hearing [60]. The authors found that acoustic discomfort occurred when a train passed in the middle of the tunnel [60].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Regarding the relationship between noise, train stations and tunnels in terms of public health, Xie, Peng, Wang, and Zhang conducted experiments in tunnels to examine the effects of high-speed rails on hearing [60]. The authors found that acoustic discomfort occurred when a train passed in the middle of the tunnel [60]. In a similar study, Maclachlan, Ögren, van Kempen, Hussain-Alkhateeb, and Persson Waye (2018) examined the relationship between annoyance and rail vibrations while considering neighborhood distance to analyze public health implications by using a self-reported questionnaire of 6894 persons in Sweden [61].…”
Section: Literature Reviewmentioning
confidence: 99%
“…[5][6][7][8][9] The non-sealed design of metro trains allows external pressure fluctuations to enter the carriages through gaps such as air conditioning systems and doors, affecting passenger comfort and potentially leading to symptoms such as ringing and ear pain. [10][11][12][13][14][15] Therefore, in order to enhance the operational speed and passenger comfort of metro trains, a thorough investigation into the airtightness of metro trains is urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…Tinnitus happens in passengers and even eardrum damage might occur. [14][15][16] In vehicle tests, it is hard to repeat the service environment in full-lifecycle, and primarily of high cost. Hence, laboratory test becomes a popular way to simulate pressure change.…”
Section: Introductionmentioning
confidence: 99%